Performing boundary work: The emergence of a new practice in a hybrid operating room. (June 2017) - Lindberg, Kajsa; Walter, Lars; Raviola, Elena
Abstract: This paper addresses the processes of boundary work, in relation to the introduction of new technology, unfolding during the emergence of new medical practices. Inspired by Gieryn's fluid and practical view of boundaries and boundary work, and by Actor-Network Theory's description of scripting processes, we study the processes of negotiating and (re-)constructing boundaries in order to reveal both the interactions between different kinds of boundary work and their situatedness in the context of the emerging practice. We conducted a longitudinal and qualitative study of a generic Hybrid Operating Room at a Swedish university hospital, where sophisticated imaging devices are combined with open surgery procedures in a single room; consequently, medical requirements regarding radiology, surgery and anesthesia, as well as the specificities of the new technology, all need to be met at the same time. The study shows how the visibility of boundaries is a result of as well as a condition for boundary work, how boundary work is a dynamic and iterative process, and how it unfolds in a recursive relationship between practice and boundaries. Highlights: A qualitative study of the emergence of a new practice in a Hybrid OR. Boundaries emerge through practice, rather than being a priori constructions. Boundary work is a dynamic and iterative process. Boundary work builds on a recursive relationship between practice and boundaries. Disciplinary boundaries are negotiated in relation to practice and technology.